The Indonesian-Moderate Muslim Communities Opinion on Social Media Hate Speech - Husni, Husni; Bisri, Hasan (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to discover the Indonesian-moderate Muslim communities opinion on social media hate speech. The qualitative research data on 73 Indonesian-moderate Muslim figures in West Java was collected by direct interviews, via email, social media, telephone calls, and from their opinions in various media. The results showed that Indonesian-moderate Muslim leaders in West Java uphold and respect freedom of expression as one of the basic human rights, but they refuse if this right is misused to spread hate speech. They also agree with the importance of rules and law enforcement to overcome the problem of spreading hate speech, but according to them, the legal aspect is not the only approach. They view multicultural education as a long-term strategy to build a mature democratic society with high ethical standards.